Did Egyptian Women Win or Lose by Overthrowing the Regime of Hosni Mubarak? - Rogowska, Blanka (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
Egypt is a place with a long tradition of female participation in revolutions. After years of Mubarak’s despotism, women joined the revolution once again. As a result, they had to deal with the violation of women’s rights. When Morsi was removed, women were again at the top of political topics. The new constitution was described as the most progressive for women. Sisi has been a president for short time but he is already called the president of women. However women still face problems. They defended themselves from the Muslim Brotherhood’s rules by supporting Sisi, but did they really win by overthrowing the regime of Mubarak?